PEMIKIRAN SYAUQI DHAIF DAN UPAYA PEMBAHARUANNYA DI BIDANG PENGAJARAN NAHWU (Telaah Buku Tajdid al-Nahwi Karya Syauqi Dhaif) - Eva Ardinal (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2013)
Science of Nahwu is recognized as a discipline that is loaded with a variety of rules and theories, as the result of a process of a long journey in the history of Arabic linguistics. Starting from the codification and systemization activities of Arabic vocabulary is quite time consuming, then linguists (al-Lughawiyyûn / linguist) construct and lay the basic principles of the rules of the language. The basic principles of nahwu at first is very simple then evolved into a